2020
DOI: 10.1090/conm/746/15010
|View full text |Cite
|
Sign up to set email alerts
|

A topological study of protein folding kinetics

Abstract: F ocusing on a small set of proteins that i) fold in a concerted, all-or-none (twostate) fashion and ii) do not contain knots or slipknots, we show that the Gauss linking integral, the torsion and the number of sequence-distant contacts provide information regarding the folding rate. Our results suggest that the global topology/geometry of the proteins shifts from right-handed to left-handed with decreasing folding rate, and that this topological change is associated with an increase in the number of more sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…We analyze a set of simple, single domain, non-disulfide-bonded proteins that have been reported to fold in a concerted, all-or-none, two-state fashion, whose experimental folding rates in water were obtained in [29]. In [25] it was shown that the logarithm of the experimental folding rate decreases with decreasing global Writhe and Torsion of the protein backbone. In this section we examine how the total local topological free energy correlates with folding rate.…”
Section: Local Topological Free Energy and Protein Folding Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyze a set of simple, single domain, non-disulfide-bonded proteins that have been reported to fold in a concerted, all-or-none, two-state fashion, whose experimental folding rates in water were obtained in [29]. In [25] it was shown that the logarithm of the experimental folding rate decreases with decreasing global Writhe and Torsion of the protein backbone. In this section we examine how the total local topological free energy correlates with folding rate.…”
Section: Local Topological Free Energy and Protein Folding Ratesmentioning
confidence: 99%
“…Studies have applied the Gauss linking integral to measure the entanglement of the protein backbone by taking the entire backbone of the protein or by looking at linking between parts of the protein. Both approaches have found a correlation between folding rates and these measures of conformational complexity [5][6][7]25]. However, this does not answer how local properties of proteins relate to its tertiary structure.…”
Section: Introductionmentioning
confidence: 98%
“…More precisely, it was shown that the writhe in combination with the Z1 algorithm can provide a new estimator of the entanglement length with several advantages over other estimators and our proposed measures have also been used to understand the dis-entanglement of polymer chains in a melt under an elongational force [36,37,38]. Recently, the Gauss linking integral has been also used to study protein folding kinetics [39]. These results indicate the promise of such topology-based estimators in polymer theories.…”
Section: Introductionmentioning
confidence: 99%
“…Our proof-of-concept-the restricted and unrestricted searches-and rar0 make use only of the writhe for identifying locally entangled configurations. Several authors have recently made similar use of the writhe, but for defining a global entanglement of one or more polymers (Baiesi et al, 2016;Baiesi et al, 2017;Baiesi et al, 2019;Panagiotou & Kröger, 2014;Panagiotou, Kröger & Millett, 2013;Panagiotou & Plaxco, 2019;Panagiotou, Millett & Atzberger, 2019). A general aim there is to relate such an entanglement measure to physical properties of the molecules.…”
mentioning
confidence: 99%
“…A general aim there is to relate such an entanglement measure to physical properties of the molecules. In these works the writhe is applied to open curves (Baiesi et al, 2016;Panagiotou & Kröger, 2014;Panagiotou, Kröger & Millett, 2013;Panagiotou & Plaxco, 2019;Panagiotou, Millett & Atzberger, 2019). Closest to our application of the local writhe numbers are Baiesi et al (2017); Baiesi et al (2019).…”
mentioning
confidence: 99%